2010
DOI: 10.1111/j.1440-1843.2010.01771.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic abnormalities in adults with cystic fibrosis

Abstract: Abnormalities of glucose metabolism are highly prevalent in CF patients, and are accompanied by hypertriglyceridaemia in the 30-39 years age group. Prospective studies are required to confirm lipid abnormalities and investigate possible cardiovascular complications in patients with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 39 publications
(60 reference statements)
4
32
0
Order By: Relevance
“…This is important because the risk of macrovascular disease has shaped treatment and therapy recommendations for persons with type 1 and type 2 diabetes; many of these recommendations are not relevant in CF and may even be harmful. Cholesterol levels are generally low in CF, but isolated triglyceride elevation is not uncommon . Lipid elevation may be more common after lung transplantation and in older patients with less severe CF mutations.…”
Section: Survival and Prognosismentioning
confidence: 99%
“…This is important because the risk of macrovascular disease has shaped treatment and therapy recommendations for persons with type 1 and type 2 diabetes; many of these recommendations are not relevant in CF and may even be harmful. Cholesterol levels are generally low in CF, but isolated triglyceride elevation is not uncommon . Lipid elevation may be more common after lung transplantation and in older patients with less severe CF mutations.…”
Section: Survival and Prognosismentioning
confidence: 99%
“…70 A study from London reported retinopathy, but also that no macrovascular complications were found. 31 Georgiopoulou et al 71 may have provided much of the explanation. In their study of metabolic aspects of CF, they noted that total and low-density lipoprotein cholesterol were low (total cholesterol 3.5 mmol/l, low-density lipoprotein 1.27 mmol/l), but that high-density lipoprotein cholesterol was near normal.…”
Section: Complicationsmentioning
confidence: 99%
“…Recent studies have demonstrated the application of lipidomics in studies investigating diabetes, cystic fibrosis, respiratory diseases and neurodegenerative diseases. These studies have clearly indicated the potential usefulness of lipidomics both to generate biomarkers of disease and to probe signalling and metabolic processes [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%